Callus induction and Agrobacterium tumefaciens mediated transfer of hydroxy methyl glutaryl CoA reductase (HMGR) gene in Centella asiatica L. - Lekshmi, R.S.; Soni, K.B.; Alex, Swapna; Rajmohan, K.; Anith, K.N. (Journal of Tropical Agriculture, 2014)
Centella asiatica is an important medicinal plant, possessing a blend of compounds including triterpenes. Among the various secondary metabolites, triterpenes have remarkable pharmaceutical value due to their anti inflammatory, antitumour, neuroprotective, skin care and toning effects. But the quantity of triterpenes in Indian ecotypes is very low. In the present study, an attempt was made to transfer HMGR gene, encoding one of the key enzymes involved in triterpene biosynthesis, to C. asiatica. Callus cultures ofC. asiatica were established in MS medium with Kn 4 mgl-1 and NAA 2 mgl-1 and the regeneration of callus was obtained in MS medium supplemented with Kn 4 mgl-1 and NAA 2 mgl-1. Agrobacterium tumefaciens strain EHA 105 harbouring the plasmid pBE2113 containing nptll and hmgr gene was used for transformation of callus and the transformation was confirmed by PCR .